MODIFIKASI PEMBELAJARAN STATISTIKA MELALUI PENDEKATAN KONTEKSTUAL DENGAN SENTUHAN HUMOR - Triyanto, Triyanto (Jurnal Inovasi Pendidikan, 2010)
This research is aimed at applying the contextual and humorous approach in teaching Method of Statistics I, at the Mathematics Department of Teacher Training and Education Faculty, Sebelas Maret University Surakarta. It is hoped that the teaching quality will be increased. It is a kind of development research with the 4-D model. In its implementation, this research uses a descriptive qualitative method in order to know the effectiveness of applying the contextual and humorous approach in teaching Method of Statistics I. The population is all of the students in the Mathematics Department of Teacher Training and Education Faculty, Sebelas Maret University Surakarta, whereas the sample is 80 students taken randomly. Forty students were treated as the experimental group, while the other forty were treated as the controlled group. The results of this research show that: (1) there is peripheral [insignificant] learning improvement; and (2) there is positive influence of the contextual and humorous approach in teaching Method of Statistics I at the Mathematics Department of Teacher Training and Education Faculty, Sebelas Maret University Surakarta.